LOW-INTENSITY LASER RADIATION IN CORRECTION OF BLOOD HEMODYNAMIC AND RHEOLOGICAL PARAMETERS AFTER SURGERY FOR HEAD AND NECK CANCER - Yu. Yu. Gorchak; M. L. Stakhanov; G. P. Gens; K. A. Firsov; D. N. Reshetov; S. M. Gainedinov; A. A. Kurnosov; A. Yu. Korobkova; L. I. Korobkova (Сибирский онкологический журнал)
Purpose: to study the effect of low-level laser therapy (LLLT) in correction of blood hemodynamic and rheological parameters after surgery for head and neck cancer.Material and Methods. The study included 134 head and neck cancer patients with a median age of 54.24 ± 12.7 years (range: 23–78 years). There were 39 (29.1 %) men and 95 (70.9 %) women. To assess the effectiveness of LLLT, all patients were divided into 3 groups. Group I included 45 patients, who received conventional therapy without the use of LLLT. Group II consisted of 45 patients, who received conventional therapy in combination with LLLT. Group III included 44 patients, who received LLLT alone. Azor 2K-02 was used as a source of LLLT in the red to near infrared spectral range. Characteristics of blood flow in the vessels of the neck and the rheological properties of blood, as well as the parameters of spontaneous platelet aggregation and the content of soluble fibrinmonomer complexes in the blood plasma of patients were studied.Results. The data obtained indicated that the use of LLLT promoted normalization of blood rheological properties in patients, who underwent surgery. Normalization of blood rheological properties occurred faster and lasted for a longer period. In patients, who received conventional therapy in combination with LLLT, the hemodynamic and rheological parameters of blood were improved 2–14 days after therapy, whereas in patients receiving conventional therapy alone, this improvement was seen 30 or more days after therapy.Conclusion. LLLT in combination with conventional therapy was shown to have a positive effect on hemodynamic and rheological parameters after surgery for head and neck cancer.